Efficient removal of doxycycline using Schwertmannite as a heterogeneous Fenton-like catalyst over a wide pH range. Issue 2 (April 2023) - Tian, Yu; Liu, Fenwu; Sun, Bo; Tong, Zhenye; Fu, Peng; Zhang, Jingzhi; Bi, Wenlong; Xu, Shaozu; Pei, Guangpeng
Abstract: Residual doxycycline (DOX) in the aquatic environment has received a considerable amount of critical attention due to its toxicity and widespread distribution in the environment. This study explored a simplified and rapid method to remove DOX over a wide pH range (pH = 2–10). Schwertmannite (SCH) was synthesized using biological methods to remove DOX in combination with H2 O2 . The results showed that 98.52% of DOX and 57.35% of total organic carbon (TOC) was removed over 30 min at 50 ºC without any external energy input, where the addition of SCH and H2 O2 was 1.6 g/L and 71 mg/L, respectively. Meanwhile, the DOX removal efficiency was 98.18% at 50 ºC over 30 min and 97.70% of DOX could even be removed at 10 ºC when the reaction time was prolonged to 120 min. Hydroxyl radicals (·OH) were the main oxidative species. Moreover, the removal efficiencies of DOX after 3 h in the SCH/H2 O2 system were 26.97%, 31.54%, 39.23%, 47.07%, 68.43%, 88.92%, and 97.64% in actual aquaculture wastewater when the COD concentrations was 7000, 5000, 3000, 1000, 500, 200, and 100 mg/L, respectively. The results of this study provided a simple and rapid method for removing DOX from DOX-containing wastewater. Graphical Abstract: ga1 Highlights: Schwertmannite is used as a Fenton-like catalyst for doxycycline(DOX) removal. The DOX degradation system works well in a wide pH range 2–10. The DOX removal process has a strong temperature adaptability in 10 ºC–50 ºC. The Fenton-like system has a good removal effect on DOX in actual wastewater.